White Blood Cell, Hemoglobin and Platelet Distribution Width as Short-Term Prognostic Markers in Patients with Acute Myocardial Infarction - Bae, Myung Hwan; Lee, Jang Hoon; Yang, Dong Heon; Park, Hun Sik; Cho, Yongkeun; Chae, Shung Chull (Journal of Korean medical science, 2014)
The aim of this study was to assess the prognostic value of combined use of white blood cell (WBC), hemoglobin (Hb), and platelet distribution width (PDW) in patients with acute myocardial infarction (AMI). This study included 1,332 consecutive patients with AMI. Patients were categorized into complete blood cell (CBC) group 0 (n=346, 26.0%), 1 (n=622, 46.7%), 2 (n=324, 24.3%), and 3 (n=40, 3.0%) according to the sum of the value defined by the cut-off levels of WBC (1, ≥ 14.5 × 10(3)/µL; 0, <14.5 × 10(3)/µL), Hb (1, <12.7 g/dL; 0, ≥ 12.7 g/dL), and PDW (1, ≥ 51.2%; 0: <51.2%). In-hospital death occurred in 59 (4.4%) patients. Patients who died during index hospitalization had higher WBC and PDW and lower Hb. The patients could be stratified for in-hospital mortality according to CBC group; 1.2%, 2.7%, 9.0%, and 22.5% in CBC groups 0, 1, 2, and 3 (P<0.001), respectively. In multivariate logistic regression analysis, CBC group ≥ 2 (odds ratio, 3.604; 95% confidence interval, 1.040-14.484, P=0.043) was an independent predictor for in-hospital death. The prognostic impact of the combined use of CBC markers remained significant over 12 months. In conclusions, combination of WBC, Hb, and PDW, a cheap and simple hematologic marker, is useful in early risk stratification of patients with AMI.